2001
DOI: 10.3758/bf03195369
|View full text |Cite
|
Sign up to set email alerts
|

Methodological variables in Web-based research that may affect results: Sample type, monetary incentives, and personal information

Abstract: There are many methodological differences between Web-based studies, differences that could substantially affect the results. The present study investigated whether sample type, offering payment through a lottery, and requiring participants to enter personal information would affect dropout rates and/or the substantive results in a study of jury decision making in capital cases. Asking participants to enter their e-mail addresses increased dropout rates, and offering payment through a lottery tended to do so a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
3
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 24 publications
1
64
3
2
Order By: Relevance
“…First, would we find the same pattern of effects for learning the opposite effect (O'Neil & Penrod, 2001). Pilot testing of instructions and providing contact information for questions (Michalak & Szabo, 1998) may also reduce dropout.…”
Section: The Gizmo Problem-solving Taskmentioning
confidence: 99%
“…First, would we find the same pattern of effects for learning the opposite effect (O'Neil & Penrod, 2001). Pilot testing of instructions and providing contact information for questions (Michalak & Szabo, 1998) may also reduce dropout.…”
Section: The Gizmo Problem-solving Taskmentioning
confidence: 99%
“…The first study sought to replicate the effects of sample type and financial incentives shown in previous studies (Frick et al, 1999;K. M. O'Neil & Penrod, 2001) and to explore the impact of two new methodologicalvariablesmethod of obtaining consent and Web page table design.…”
Section: Studymentioning
confidence: 99%
“…Brevity is desirable because in a psychological experiment the MIP often precedes the actual experiment and should not take time from it. Third, the MIP should not contain elements that prevent potential participants from taking part because their computer hardware or software or their connection to the Internet does not support the experiment (O'Neil & Penrod, 2001). Fourth, there should be no difference in dropout rates between the negative and the positive mood induction (Göritz, 2002;Göritz & Moser, 2006).…”
Section: Demands On An Online Mipmentioning
confidence: 99%